2019
DOI: 10.1007/s10147-019-01435-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SERPINE1, PLAU and ACTA1 as biomarkers of head and neck squamous cell carcinoma based on integrated bioinformatics analysis

Abstract: Background Head and neck squamous cell carcinoma (HNSCC) is the six leading cancer by incidence worldwide. The 5-year survival rate of HNSCC patients remains less than 65% due to lack of symptoms in the early stage. Hence, biomarkers which can improve detection of HNSCC should improve clinical outcome. Methods Gene expression profiles (GSE6631, GSE58911) and the Cancer Genome Atlas (TCGA) HNSCC data were used for integrated bioinformatics analysis; the differentially ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 33 publications
4
65
0
Order By: Relevance
“…Consistent with our results, pathological stagerelated hub gene role of COL1A1, COL1A2, COL5A1 were reported earlier by another group [43]. The hub gene role of ACTA1 was found in prostate cancer [44] and the prognostic role of ACTA1 was found in head and neck squamous cell carcinoma (HNSCC) [45]. The important role of DCN in cancer was mentioned by several studies.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our results, pathological stagerelated hub gene role of COL1A1, COL1A2, COL5A1 were reported earlier by another group [43]. The hub gene role of ACTA1 was found in prostate cancer [44] and the prognostic role of ACTA1 was found in head and neck squamous cell carcinoma (HNSCC) [45]. The important role of DCN in cancer was mentioned by several studies.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our results, pathological stagerelated hub gene role of COL1A1, COL1A2, COL5A1 were reported earlier by another group [43]. The hub gene role of ACTA1 was found in prostate cancer [44] and the prognostic role of ACTA1 was found in head and neck squamous cell carcinoma (HNSCC) [45]. The experimental study suggests that Decorin does not affect directly anti-tumoural immune response, yet is required for e cient invasiveness in vitro [46].…”
Section: Discussionsupporting
confidence: 91%
“…PDGFA, a member of the platelet-derived growth factor (PDGF) family, may play a crucial role in the composition of the immune microenvironment 20 . PLAU, one of the major proteolytic enzymes involved in the degradation of extracellular matrix, has been demonstrated to play a critical role in tissue remodeling and migration in the developmental of cancer and in tumorigenesis 21 . Some studies indicated that PLAU was a marker to predict OS in HNSCC patients 22 .…”
Section: Discussionmentioning
confidence: 99%